Comprehensive Analysis of Sinonasal Inverted Papilloma Expression Profiles Identifies Long Non-Coding RNA AKTIP as a Potential Biomarker - He, Hanyi; Wang, Xinlu; Lu, Yueyue; Lin, Xiaojiang; Li, Yuandong; Li, Yong; Lin, Zhihong; Ma, Zhiqi; Cao, Xiaolin; Teng, Yaoshu (Frontiers in Genetics, 2022)
Long noncoding RNAs (lncRNAs) are a novel class of potential biomarkers and therapeutic targets for the treatment of neoplasms. The purpose of this study was to explore the expression profile, potential functions, and diagnostic and clinical significance of lncRNAs in sinonasal inverted papilloma (SNIP). The expression profiles of lncRNAs and mRNAs were analyzed using a microarray. The potential functions and clinical implications of specific lncRNAs were further analyzed by bioinformatics and statistical methods. Microarray analysis identified 1,668 significantly upregulated and 1,767 downregulated lncRNAs in SNIP. Several mRNAs coexpressed with lncRNAs were enriched in some biological processes and cellular signaling pathways related to tumorigenesis. Lnc-AKTIP might interact with a variety of tumor-associated proteins and transcription factors, such as PCBP2, IRF-1, and p53. Receiver operating characteristic curve analysis for lnc-AKTIP showed an area under the curve of 0.939. Notably, its expression level was significantly decreased in SNIP tissues versus normal tissues and was associated with SNIP staging. Lnc-AKTIP may serve as a valuable diagnostic biomarker and a therapeutic target for SNIP.